Peningkatan Kinerja Simpang Ciceri, Kota Serang dengan Model Penerapan Ruang Henti Khusus - Hanida, Shelia Ayu Rida; Hadi, Suprapto; Aprianto, Rizal (Kadiri University, 2024)
The Ciceri intersection is in a densely populated urban area characterized by heavy traffic, particularly motorbikes. This is due to the nearby educational institutions, shops, offices, and a shopping center. The intersection faces numerous traffic conflicts, including crowded vehicle queues, irregular queuing by motorbikes, and improper lane usage by two- and four-wheeled vehicles. The phase setting of traffic signaling devices (APILL) at the Ciceri intersection has been implemented but has not solved the problem. This research aims to analyze the use of RHK to improve the performance of the Ciceri intersection using the Vissim model. The method is to test or simulate various RHK models at the research location. The results obtained can be applied to the RHK at two intersection legs, namely east and west, with a box-type RHK measuring 8m long and 2 x 3.5m wide, increasing the level of Service (LOS) from E to F. The results show a reduction in queues of 5.64 m and delays of 1.52 seconds on the north leg, as well as a reduction in queues of 7.85 m and a delay of 13.48 seconds on the south leg. These results show that RHK can effectively improve the performance of intersections with high traffic volumes without the need to increase physical road capacity.